This preview shows page 1. Sign up to view the full content.
Unformatted text preview: = P(F) = P(BHH) = 0.5 So P(BHH) = P(B int HH) / P(BHH) = P(BHH) / P(HH) = 0.5 / P(HH). But what is P(HH)? HH = BHH u FHH, so P(HH) = P(FHH) + P(BHH) = 1/8 + 1/2 = 5/8 So P(BHH) = 0.5 / 5/8 = 4/5 = 0.80 = 80%
Bayes Theorem: P(E'E) = P(EE') P(E') / P(E) Proof: P(E'E) = P(E' int E) / PE) and P(EE') = P(E' int E) / P(E'), so P(E' int E) = P(E) P(E'E) = P(E') P(EE') and thus P(E'E) = P(E') P(EE') / P(E)
Random Variables: functions X:S
> R
Idea is that associated with an outcome there may be additional quantities of interest.
Example: Suppose a social scientist suspects that a student's age plus their GPA is significant for their getting a summer job. This suggests considering the...
View
Full
Document
This note was uploaded on 01/13/2012 for the course CMSC 250 taught by Professor Staff during the Summer '08 term at Maryland.
 Summer '08
 staff

Click to edit the document details